Hukum Kasih: Landasan Bersama Agama-agama - Frits Octavianus Tatilu (Societas Dei: Jurnal Agama dan Masyarakat, 2017)
ABSTRACT: This article wich is entitled as "The Law of Love: A Joint Foundation of Religions" focuses on how the low of love is able to be applied in the joint life of religions in Indonesia, especially as a joint foundations in the formulation of non-discriminatory policy be it in central government or in local government. Firstly, it will be discussed about the understanding of the law of love Christian perspective, and then it will be also discussed about views of religions related with the law of love. The writer supposes that the law of love is able to be a joint foundations of religions, as well as be applied in the formulation of non-discriminatory public policy. KEYWORDS: the law of love, religious, joint foundations, discrimination